Characteristics of Women Diagnosed With Preeclampsia With Severe Features Based on Hypertension Alone [05L]. (May 2020) - Romagano, Matthew P.; Flint, Matthew; Sachdev, Devika; Apuzzio, Joseph; Williams, Shauna F.; Gittens-Williams, Lisa
Abstract : INTRODUCTION: The objective of this study was to compare pregnancy and postpartum characteristics amongst women diagnosed with preeclampsia with severe features (PE-SF) based on hypertension alone versus those with additional criteria for PE-SF. METHODS: This is an IRB-approved retrospective cohort study of women with a diagnosis of PE-SF, identified by hospital discharge records over a 1-year period. Electronic medical records were reviewed. Women diagnosed with PE-SF based on severe hypertension alone (HTN-A) in the absence of other criteria for preeclampsia were compared to those with PE-SF that had additional criteria for preeclampsia (e.g. proteinuria or clinical/laboratory signs or symptoms). RESULTS: 105 women had PE-SF or chronic hypertension with superimposed PE-SF over the study period. 22 (21%) of these women were diagnosed based on HTN-A. Maternal demographics, intrapartum/postpartum characteristics, laboratory values, delivery outcomes, and postpartum follow-up rates were similar. Those diagnosed with PE-SF based on HTN-A had a lower mean protein-to-creatinine ratio (0.2 vs 1.5, P= .003). For women who attended a 1-week postpartum blood pressure check, the rate of those with severe hypertension were similar between the HTN-A and other criteria groups (2/12 vs 3/49, P= .233) but the HTN-A group was more likely to have severe hypertension at the 3-4 week postpartum visit (4/13, 31% vs 2/57, 3.5%, P= .009). CONCLUSION: Women who receive a diagnosis of PE-SF based on severe hypertension alone in the absence of other abnormal findings still have a significant rate of persistent hypertension postpartum. These women should be followed and managed for persistent hypertensive disease in the postpartum period and beyond.